SERR spectroelectrochemical study of cytochrome cd1 nitrite reductase co-immobilized with physiological redox partner cytochrome c552 on biocompatible metal electrodes - Silveira, Célia M.; Quintas, Pedro O.; Moura, Isabel; Moura, José J. G.; Hildebrandt, Peter; Almeida, M. Gabriela; Todorovic, Smilja (PLoS, 2015)
"Cytochrome cd1 nitrite reductases (cd1NiRs) catalyze the one-electron reduction of nitrite to nitric oxide. Due to their catalytic reaction, cd1NiRs are regarded as promising components for biosensing, bioremediation and biotechnological applications. Motivated by earlier findings that catalytic activity of cd1NiR from Marinobacter hydrocarbonoclasticus (Mhcd1) depends on the presence of its physiological redox partner, cytochrome c552 (cyt c552), we show here a detailed surface enhanced resonance Raman characterization of Mhcd1 and cyt c552 attached to biocompatible electrodes in conditions which allow direct electron transfer between the conducting support and immobilized proteins. Mhcd1 and cyt c552 are co-immobilized on silver electrodes coated with self-assembled monolayers (SAMs) and the electrocatalytic activity of Ag // SAM // Mhcd1 // cyt c552 and Ag // SAM // cyt c552 // Mhcd1 constructs is tested in the presence of nitrite. Simultaneous evaluation of structural and thermodynamic properties of the immobilized proteins reveals that cyt c552 retains its native properties, while the redox potential of apparently intact Mhcd1 undergoes a ~150 mV negative shift upon adsorption. Neither of the immobilization strategies results in an active Mhcd1, reinforcing the idea that subtle and very specific interactions between Mhcd1 and cyt c552 govern efficient intermolecular electron transfer and catalytic activity of Mhcd1."
© 2015 Silveira et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Cytochrome cd1 nitrite reductases; Marinobacter hydrocarbonoclasticus